Tunable non-Lifshitz–Kosevich temperature dependence of Shubnikov–de Haas oscillation amplitudes in SmSb - Wei Zhang; C. N. Kuo; S. T. Kuo; Chun Wa So; Jianyu Xie; Kwing To Lai; Wing Chi Yu; C. S. Lue; Hoi Chun Po; Swee K. Goh (npj Quantum Materials, 2023)
Abstract The Lifshitz–Kosevich (LK) theory is the pillar of magnetic quantum oscillations, which have been extensively applied to characterise a wide range of metallic states. In this study, we focus on the Shubnikov–de Haas (SdH) effect observed in SmSb, a rare-earth monopnictide. We observed a significant departure from the expected LK theory near T N  = 2.4 K: both a peak-like anomaly and an enhancement in the temperature dependence of quantum oscillation amplitude are seen in SmSb. Moreover, we discovered a remarkable sensitivity of the SdH amplitudes to sample purity. By adjusting the sample purity, we were able to tune the temperature dependence of the α band’s SdH amplitudes from a peak-like anomalous behaviour to an enhancement. Therefore, SdH oscillations from the α band connect the two well-known non-LK behaviours, controllable through varying the sample purity, paving the way for developing further understanding of the mechanism leading to the anomalous quantum oscillations.